Unusual highly diastereoselective Rh(II)-catalyzed dimerization of 3-diazo-2-arylidenesuccinimides provides access to a new dibenzazulene scaffold - Vepreva, Anastasia; Bunev, Alexander S.; Kudinov, Andrey Yu.; Kantin, Grigory; Krasavin, Mikhail; Dar’in, Dmitry (Beilstein Journal of Organic Chemistry, 2022)
Formation of unusual unsymmetrical dimers or/and indenes via Rh2(esp)2-catalyzed decomposition of 3-diazo-2-arylidenesuccinimides has been investigated. The reaction proceeded under mild conditions, and its result was shown to strongly depend on the nature of the substituents in the diazo substrate. The new reaction provides access to dibenzoazulenodipyrrole and indenopyrrole derivatives in moderate to high yield. Dibenzoazulenodipyrroles bearing alkyl substituents at the nitrogen atom showed pronounced cytotoxocity against the A549 human lung adenocarcinoma cell line while N-aryl analogs were non-cytotoxic.
Keywords: diazo arylidene succinimides; dibenzoazulenodipyrroles; indenopyrroles; Rh2(esp)2-catalyzed decomposition; unsymmetrical dimers